Obcowanie z obcymi. O ludzko-obcych hybrydach w Wojnie światów Herberta George’a Wellsa i Drakuli Brama Stokera: Align with aliens. About human-alien hybrids in H.G. Wells’ War of the Worlds and B. Stoker’s Dracula - Marcela, Mikołaj (Zagadnienia Rodzajów Literackich / The Problems of Literary Genres, 2019)
Berhard Waldenfels claimed that at the turn of 18th and 19th century “the alien explicitly and definitely penetrated the heart of the reason and the heart of the one’s own” in Western culture. Since then we no longer live in a world, where we could be fully ourselves. But the alien still haunts us and raises fear. A hundred years later, at the turn of 19th and 20th century, British literature presented two powerful images of confrontation with the alien, images that penetrated the imagination of the mass audience in 20th and 21st century: Martians from H.G. Wells’ famous novel and the iconic bloodthirsty count created by B. Stoker. Though they seemingly radically differ from humans at a close look they make us rethink our definition of humanity and of the alien.